19.28% Efficiency and Stable Polymer Solar Cells Enabled by Introducing an NIR‐Absorbing Guest Acceptor. (6th January 2023) - Fan, Qunping; Ma, Ruijie; Bi, Zhaozhao; Liao, Xunfan; Wu, Baohua; Zhang, Sen; Su, Wenyan; Fang, Jin; Zhao, Chao; Yan, Cenqi; Chen, Kai; Li, Yuxiang; et al.
Abstract: Here, a near‐infrared (NIR)‐absorbing small‐molecule acceptor (SMA) Y‐SeNF with strong intermolecular interaction and crystallinity is developed by combining selenophene‐fused core with naphthalene‐containing end‐group, and then as a custom‐tailor guest acceptor is incorporated into the binary PM6:L8‐BO host system. Y‐SeNF shows a 65 nm red‐shifted absorption compared to L8‐BO. Thanks to the strong crystallinity and intermolecular interaction of Y‐SeNF, the morphology of PM6:L8‐BO:Y‐SeNF can be precisely regulated by introducing Y‐SeNF, achieving improved charge‐transporting and suppressed non‐radiative energy loss. Consequently, ternary polymer solar cells (PSCs) offer an impressive device efficiency of 19.28% with both high photovoltage (0.873 V) and photocurrent (27.88 mA cm −2 ), which is one of the highest efficiencies in reported single‐junction PSCs. Notably, ternary PSC has excellent stability under maximum‐power‐point tracking for even over 200 h, which is better than its parental binary devices. The study provides a novel strategy to construct NIR‐absorbing SMA for efficient and stable PSCs toward practical applications. Abstract : A novel small‐molecule acceptor Y‐SeNF with selenophene‐fused core and naphthalene‐fused end‐groups is developed. Introducing NIR‐absorbing Y‐SeNF as a custom‐tailor guest into PM6:L8‐BO host system, ternary PSCs achieve a high efficiency of 19.28% and excellent stability.